Ventriloquism As A Medium For Strengthening Islamic Values And Character Education - Aziz, Abdul; Maryati, Sri; Nur Azizah, Fifi; Malintang, Jimmy; Fahmi, Fahmi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Ventriloquism-based instructional innovation introduces a performative dialogic medium that merges cognitive, affective, moral, and social dimensions of learning into a unified interactive experience. By positioning the puppet as a “dialogue partner,” the approach creates psychologically safe communication spaces, reduces speaking anxiety, and transforms abstract concepts into personified narratives. This qualitative field study examines the pedagogical role of ventriloquism-based instruction in strengthening classroom engagement and value internalization in secondary-level Islamic Education (PAI). Using classroom observations, semi-structured interviews, and document analysis, the study explores how puppetry mediates teacher–student interaction and shapes students’ learning experiences. The findings reveal that ventriloquism enhances behavioral, emotional, and cognitive engagement by reducing affective barriers, fostering dialogic participation, and creating an emotionally safe learning environment. The puppet functions not merely as an entertaining medium but also as an instructional mediator that builds students’ confidence to speak, models polite and ethical questioning, and supports empathetic communication aligned with prophetic pedagogical values (adab al-hiwār). The results align with multidimensional engagement theory, social learning and self-efficacy development, sociocultural mediation within the Zone of Proximal Development, multimedia learning principles, and embodied cognition perspectives. This theoretical convergence positions ventriloquism as an integrated pedagogical strategy rather than a peripheral creative technique. The study contributes to the field by framing ventriloquism as a low-cost, teacher-driven instructional innovation that harmonizes creative performative media with Islamic educational values. Although limited to a single case study, the findings offer a foundation for future comparative, longitudinal, and mixed-method research on creative pedagogies in value-based education.